POLA ALIRAN INFORMASI KOMUNIKASI DAKWAH KULTURAL MUHAMMADIYAH (Studi Kasus Tentang Komunikasi Organisasi Muhammadiyah Dalam Proses Penyebaran Pesan Dakwah Kultural Sebagai Strategi Pemberdayaan Masyarakat dan Penanaman Nilai-Nilai Islam) - Nurrohmah, Arina (Transformasi, 2017)
To change and neutralize attitudes and thoughts about Muhammadiyah which is considered anticultureand tend to be rigid, after KH. Ahmad Dahlan, then at Tanwir Muhammadiyah in Bali,followed by Tanwir and congress in Makassar and agreed to affirm cultural dakwah as one ofda'wah approach in planting Islamic values and community empowerment. So this research ismade to know the pattern of information flow of Muhammadiyah cultural propagationcommunication is the same with cultural dakwah Walisongo and NU.This research basically uses qualitative approach with descriptive case study technique. Wherethe report obtained from the field later, either from the results of interviews, documentation andobservations described descriptively.From the result of the research, the Muhammadiyah communication pattern is detected by usingthe combination theory of information flow in Joseph A Devito's organization that is wheelpattern (Leader becomes the central figure in deciding every policy and delivering the messageformally) and Y pattern from Message Spoken by Leader but member can send and Received amessage. Where this proves the theory of communication which states in certain conditionscommunicant can exchange the role of communicator when Muhammadiyah in the lower level tochannel Islamic information with cultural approach in the area. There are five cultural da'wahstrategies: (cultural da’wah through local culture, cultural da’wah in the context of globalculture, cultural da’wah through art appreciation, cultural da’wah through multimedia, culturalda’wah through pilgrim movement and da’wah jama’ah), and prove cultural mission carriedMuhammadiyah has Covering a wider scope that suits the culture of modern society. Wider thanthe cultural dakwah of Walisongo, whose society was still traditional.Keywords: information communication flow, cultural da'wah muhammadiyah